A new journey of plastics: Towards a circular and low carbon future. (August 2022) - Li, Bin; Ma, Yichun; Li, Hui
Abstract: The plastic pollution to the environment, especially to the ocean, has been draw a lot of attention from the public which results some negative impact to the entire value chain of plastic industry. Circularity and low carbon have been perceived as the solution to tackle these challenges. Efforts required from the feedstock, polymerization, product design and recycling, are all need to be considered. Shifting to the low carbon feedstock is key to reduce the total emission of plastics, while make it recyclable is crucial to achieve low carbon emission for the entire life cycle of plastics. Mechanical recycling aims to make more post-consumer recycles (PCR) being used to some high-end applications to incentivize more plastics being collected and regenerated. The advanced recycling is the last stop for those unrecyclable, avoiding them to the undesired incineration or landfill, and generate value through the pyrolysis or gasification process. The scale is key to make it profitable and sustainable. Graphical abstract: Achieving plastic circularity would be the solution to plastic pollution and low carbon development. The industry needs to rethink how the product is designed, by considering the end-of-life destination, mechanical recycling or chemical recycling, to make something being useful, while avoiding the incineration and landfill. Innovations required to at each stage of plastic value chain aiming to make the circularity possible and low carbon. Image, graphical abstract